2019
DOI: 10.3390/ijms20020376
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Histidine Decarboxylase and Its Roles in Inflammation

Abstract: Histamine is a well-known mediator of inflammation that is released from mast cells and basophils. To date, many studies using histamine receptor antagonists have shown that histamine acts through four types of receptors: H1, H2, H3, and H4. Thus, histamine plays more roles in various diseases than had been predicted. However, our knowledge about histamine-producing cells and the molecular mechanisms underlying histamine production at inflammatory sites is still incomplete. The histamine producing enzyme, hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 85 publications
(82 reference statements)
1
46
0
Order By: Relevance
“…Histamine is a crucial inflammatory mediator produced by many cell types, such as mast cells, basophils, macrophages, and neurons [ 1 ]. In patients with allergic rhinitis (AR), the cross-linking of IgE on mast cells/basophils by antigens induces degranulation and histamine release, causing sneezing reactions, nasal discharge, and nasal obstruction [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Histamine is a crucial inflammatory mediator produced by many cell types, such as mast cells, basophils, macrophages, and neurons [ 1 ]. In patients with allergic rhinitis (AR), the cross-linking of IgE on mast cells/basophils by antigens induces degranulation and histamine release, causing sneezing reactions, nasal discharge, and nasal obstruction [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, cytokine involvement may already have occurred by the time the treatment agent was introduced, and the in ammatory response would have started shifting toward mediator synthesis and degranulation. Dexamethasone is known to strongly inhibit histamine synthesis (N Hirasawa et al, 2001;Noriyasu Hirasawa, 2019). This may explain the high rate of protection seen with dexamethasone in the therapeutic model but not the prophylactic.…”
Section: Discussionmentioning
confidence: 99%
“…The number of ECL cells found in the gastric body in our study using anti-HDC IHC was lower than the numbers of D cells found in the control group and in the PPI group, with or without HP infection. The HDC enzyme converts histidine into histamine 9 , 12 , 13 . HDC is also expressed in mastocytes and basophils, wherein histamine is stored in granules 12 , these are cells with different morphological characteristics than ECL cells.…”
Section: Discussionmentioning
confidence: 99%
“…The HDC enzyme converts histidine into histamine 9 , 12 , 13 . HDC is also expressed in mastocytes and basophils, wherein histamine is stored in granules 12 , these are cells with different morphological characteristics than ECL cells.…”
Section: Discussionmentioning
confidence: 99%